The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1159/000502658
|View full text |Cite
|
Sign up to set email alerts
|

May High Levels of Systemic Immune-Inflammation Index and Hematologic Inflammation Markers Suggest a Further Stage in Testicular Tumours?

Abstract: <b><i>Introduction:</i></b> Due to variety of treatment alternatives for testicular tumours, parameters other than existing staging criteria are also needed. Most studies have revealed the correlation between cancer and inflammation. In this study, we aimed to investigate the value of preoperative inflammatory markers between early-stage testicular tumours and patients with advanced-stage, their relationship with tumour pathology and their importance in predicting stage. To calculate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
4
17
0
1
Order By: Relevance
“…Statistically significant differences were shown between the median neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and systemic immuneinflammation index (SII) in early vs. advanced stages of seminomatous tumors, while within the nonseminomas, only a difference between the median platelet-to-lymphocyte ratio (PLR) was described. These data are in concordance with findings describing more intense immune cell infiltration in seminomatous than in nonseminomatous testicular tumors (25).…”
Section: Rationale For Immunotherapy In Testicular Cancersupporting
confidence: 92%
“…Statistically significant differences were shown between the median neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and systemic immuneinflammation index (SII) in early vs. advanced stages of seminomatous tumors, while within the nonseminomas, only a difference between the median platelet-to-lymphocyte ratio (PLR) was described. These data are in concordance with findings describing more intense immune cell infiltration in seminomatous than in nonseminomatous testicular tumors (25).…”
Section: Rationale For Immunotherapy In Testicular Cancersupporting
confidence: 92%
“…Although significant progresses have been made in terms of developing non-invasive prognostic biomarkers for CRC, the clinical appliance of the systematic inflammatory indices were regularly used, with its advantage of inexpensive, reliable, reproducible, robust and convenience 17 - 19 . Among all the systematic inflammatory indices, NLR and PLR were the most commonly used as prognostic biomarkers in CRC, which even had a discriminatory ability superior to other inflammatory biomarkers in resectable CRC 20 .…”
Section: Discussionmentioning
confidence: 99%
“…SII, a novel inflammation-based biomarker combining platelet, neutrophil and lymphocyte counts, has been reported to be associated with clinical outcomes in several malignancies in many studies [9][10][11][12]. This is the first study to report a lower SII is associated with response to CRT in patients with HF.…”
Section: Resultsmentioning
confidence: 80%
“…It is calculated by the formula platelet count x neutrophil count /lymphocyte count and may be considered a combination NLR and PLR [9]. Many recent studies have demonstrated that SII is a strong independent predictor of major adverse events and prognosis in patients with several malignancies [9][10][11][12]. Patients with higher SII have increased recurrence rates, reduced survival and worse treatment response than patients with lower SII [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation